1997
DOI: 10.1164/ajrccm.156.5.9701079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Train-of-Four and Best Clinical Assessment during Continuous Paralysis

Abstract: Train-of-four (TOF) monitoring is recommended in published guidelines during use of continuous-infusion neuromuscular blocking agents (NMB) in the intensive care unit (ICU). To test that recommendation, dual protocols were established in a medical ICU after intensive nursing education. Paralyzed patients received either TOF monitoring with a goal of three twitches or best clinical assessment while receiving atracurium by continuous infusion. Demographics and mean duration of paralysis of 20 patients in the TOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 36 publications
2
34
0
1
Order By: Relevance
“…The peripheral nerve stimulation group received less drug and recovered neuromuscular function and spontaneous ventilation faster than the control group. Nonrandomized observational studies have suggested that peripheral nerve monitoring reduces or has no effect on clinical recovery from NMBAs in the ICU (203,204).…”
Section: Rationalementioning
confidence: 99%
“…The peripheral nerve stimulation group received less drug and recovered neuromuscular function and spontaneous ventilation faster than the control group. Nonrandomized observational studies have suggested that peripheral nerve monitoring reduces or has no effect on clinical recovery from NMBAs in the ICU (203,204).…”
Section: Rationalementioning
confidence: 99%
“…Studies that have compared TOF-guided NMBA titration to titration based on subjective clinical assessments in patients with mixed indications for paralysis have yielded disparate results. Rudis et al 26 reported that lower doses of NMBAs were used and recovery from paralytic agents was faster in patients randomized to TOF-guided therapy, whereas 2 other studies 27,28 showed no difference between groups in total paralysis time, recovery time, and amount of drug used. In a randomized controlled trial 29 of 102 patients with ARDS who were given cisatracurium, Figure 4 Degree to which baseline factors or concurrent therapies are perceived to alter the risk profile of neuromuscular blocking agents.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which muscle paralysis improves oxygenation remain unclear. Indeed, muscle paralysis may reduce oxygen consumption (15,28), facilitate mechanical ventilation by preventing respiratory movements (29), and increase chest wall compliance (3). However, Conti et al (30) showed that there was no effect of NMBA on chest wall, lung, and respiratory system mechanics in 13 patients presenting with acute respiratory failure (four ARDS patients).…”
Section: Discussionmentioning
confidence: 99%